Analisis Pengaruh Atribut Influencer pada Platform Tiktok Terhadap Keputusan Pembelian - Yunita Eka Fitrianti; Aryo Pinandito; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The COVID-19 pandemic has forced businesses to switch to digital marketing activities. Businesses must rearrange the marketing strategy that will be implemented in order to continue to make profits in the midst of a pandemic. Among the various types of digital marketing that have emerged, influencer marketing has emerged as a type of marketing that grows rapidly during the pandemic. Influencer marketing involves marketing activities on social media through influential people on those platforms, known as influencers. One platform that is widely used by influencers is TikTok. With the rapid growth of influencer marketing, businesses need to identify the type of influencer that suits their product or service and target consumers. This study aims to determine influencer attributes that can influence consumer purchase decisions, especially influencers on TikTok. The influencer attributes used were perceived expertise, trustworthiness, and parasocial relationships. Data was collected by distributing survey questionnaires and analyzed using the Generalized Linear Model (GLM) method. Based on the results of data analysis, only one hypothesis that accepted, which, the parasocial relationship has a significant effect on consumer purchase decisions. This proves that TikTok users rely more on parasocial relationships with influencers to obtain credible information regarding their purchase decisions.